Assessment Of The Antifungal Bioactivity Of Aqueous Extract From Ziziphus Spina-Christi Leaves Against Candida SPP. Responsible For Vulvovaginal Candidiasis - Alyaa Hussein Talib (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The present study was aimed at gaining knowledge about the type of pathogen responsible for Vulvovaginal Candidiasis (VVC) infections and evaluating the antimicrobial activity of plant extracts against Candida spp. antibiotic resistance. 112 samples were taken from infected women with VVC of different ages from September to December 2024. All specimens were collected from Al Hussein Teaching Hospital/ Al- Thiqar- governorate. The results showed that 67 (59.82%) of all cases had positive results for Candida spp., while 45 (40.18%) had negative results. Candida spp. Isolated from VVC were C. albicans, the most prevalent 33 (49.26%), C. glabrata, 12 (17.91%), C. krusi and C. kefyr, 9 (13.43%), and C. guilliermondii, 4 (6.90%). The antifungal sensitivity of the pathogenic Candida spp. was tested against five types of antifungals, and the results showed the highest resistance to ketoconazole was 66 (98.51%) of Candida spp. Because of the presence of these physiologically active chemicals, Zizyphus spina-christi L. exhibits antimicrobial capabilities. In this study, the main aim is to study the antifungal activity of Ziziphus spina-christi leaf extract on some resistant candida and conduct analysis to confirm that the Ziziphus spina-christi leaves have phytochemical contents. Gas chromatography-mass spectrometry (GC-MS) was used to find the bioactive components present in extracts of Z. spina-christi leaves. Finally, we decided the inhibitory activity of Ziziphus spina-christi leaves extract. The extract of Ziziphus spina-christi had alkaloids, saponins, flavonoids, phenols, tannic acid, and terpenoids, according to a preliminary phytochemical screen. In addition, GC-MS analysis of the extract confirmed the presence of many beneficial chemicals. The extract showed promising antimicrobial activity for Candida spp. (C. albicans, C. glabrata,C. krusi , C. kefyr, and C. guilliermondii) . These results show that the Ziziphus spina-christi leaves extract is a valuable resource for bioactive chemicals with potential uses in a variety of biological contexts.